Microfilaruria by Dirofilaria immitis in a dog: a rare clinical pathological finding - Monobe, Marina Mitie; da Silva, Rodrigo Costa; Araujo Junior, João Pessoa [UNESP]; Takahira, Regina Kiomi [UNESP] (Springer Nature, 2017)
A 6-year-old Labrador with history of hyperpnea, respiratory distress, ascites and paraparesis, presented Dirofilaria immitis microfilariae in the blood smear, cytology of the abdominal fluid and urine. The positive samples were confirmed by multiplex-PCR (COI gene) and sequencing, and presented 98% homology to D. immitis (GenBank accession nos. KC107805.1, EU159111.1, EU163945.1, DQ358815.1, and AJ537512-1). Based on the presented results and the physiopathology of the heartworm disease, molecular techniques may be helpful and accurate in the diagnosis of the disease in vertebrates, and microfilaruria, even uncommon, should be considered on a renal failure evaluation.
Keywords: Dog; Heartworm disease; Microfilaruria; Molecular techniques